Sex-Related Discordance Between Aortic Valve Calcification and Hemodynamic Severity of Aortic Stenosis - Simard, Louis; Côté, Nancy; Dagenais François; Mathieu, Patrick; Couture, Christian; Trahan Sylvain; Bossé Yohan; Mohammadi Siamak; Pagé Sylvain; Joubert, Philippe; Clavel Marie-Annick (Circulation research, 2017)
Rationale:Calcific aortic stenosis (AS) is characterized by calcium deposition in valve leaflets. However, women present lower aortic valve calcification loads than men for the same AS hemodynamic severity.Objective:We, thus, aimed to assess sex differences in aortic valve fibrocalcific remodeling.Methods and Results:One hundred and twenty-five patients underwent Doppler echocardiography and multidetector computed tomography within 3 months before aortic valve replacement. Explanted stenotic tricuspid aortic valves were weighed, and fibrosis degree was determined. Sixty-four men and 39 women were frequency matched for age, body mass index, hypertension, renal disease, diabetes mellitus, and AS severity. Mean age (75±9 years), mean gradient (41±18 mm Hg), and indexed aortic valve area (0.41±0.12 cm2/m2) were similar between men and women (all P≥0.18). Median aortic valve calcification (1973 [1124–3490] Agatston units) and mean valve weight (2.36±0.99 g) were lower in women compared with men (both P<0.0001). Aortic valve calcification density correlated better with valve weight in men (r2=0.57; P<0.0001) than in women (r2=0.26; P=0.0008). After adjustment for age, body mass index, aortic valve calcification density, and aortic annulus diameter, female sex was an independent risk factor for higher fibrosis score in AS valves (P=0.003). Picrosirius red staining of explanted valves showed greater amount of collagen fibers (P=0.01), and Masson trichrome staining revealed a greater proportion of dense connective tissue (P=0.02) in women compared with men.Conclusions:In this series of patients with tricuspid aortic valve and similar AS severity, women have less valvular calcification but more fibrosis compared with men. These findings suggest that the pathophysiology of AS and thus potential targets for drug development may be different according to sex.